Digital Electronics Objectives Part 08

141 . A NAND gate is called a universal logic element because any logic function can be realized by NAND gates alone.

142 . The Boolean expression A𝐡𝐢 + ABΜ…Μ…Μ…Μ…CΜ…+AΜ…BCΜ… + AΜ…BΜ…C is equal to 𝐁̅ 𝐂̅+𝐀̅𝐂̅+𝑨𝐁̅.

143 . The Boolean expression ABC+AΜ…BC+ABΜ…C+ABCΜ…+AΜ…BΜ…CΜ… + AΜ…BΜ…CΜ… will be equal to 𝐂̅+𝐁̅+𝐀

144 . The Boolean expression A(A+B+C)(AΜ…+B+C)(A+BΜ…+C)(A+BΜ…+CΜ…) will be same as 𝐀(𝐁̅+𝐂).

145 . The Boolean expression (A+B+C)(A+BΜ…+CΜ…)(A+BΜ…+CΜ…)(AΜ…+BΜ…+C) can be simplified as A.

146 . The expression XY (𝑋YZ + π‘‹π‘Œπ‘ + π‘‹π‘Œπ‘ ) when simplified will become 0.

147 . The expression XY + XYZ + XY𝑍 + 𝑋YZ when simplified will become Y.

148 . The expression ABC(AB𝐢 + ABΜ…C+AΜ…BC) when simplified for no assignment of binary values will take the value 1.

149 . The expression AB + A𝐡 + A𝐢 + 𝐴𝐢 will be equal to 1.

150 . The expression of (A + BC + AB) will be 𝐀̅(𝐁̅+𝐂̅).

151 . The complement of (A+B)(B+C)(A+C) will be 𝐀̅
𝐁̅+𝐁̅𝐂̅+𝐀̅𝐂̅.

152 . The following expression when converted to sum of products from, will become (𝑨BC + A𝑩C + AC + BC).

153 . The expression ((AΜ…+C)(AΜ…+BΜ…+CΜ…)(A+BΜ…) when converted to sum of product form will become 𝐀𝐁̅+𝐀𝐂̅+𝐀𝐁𝐂+𝐀𝐁𝐂̅+𝐀̅ 𝐁𝐂+𝐁𝐂̅.

154 . The expression (A+C)(A𝐡 + AC)(𝐴𝐢 + 𝐡) when converted to sum of products from will become AB + ABC.(𝐗̅


155 . π˜Μ…π™Μ…+π—π˜Μ…π™) is the Boolean expression (in sum of products form) for a logic circuit when will have all output when X = 0, Y = 0 and Z = 1 and a O output for all other input state.

156 . for the logic diagram shown in Fig. 25 the output will be 𝑿𝒀 𝒁+𝑿𝒀𝒁.

157 . XY + X𝑍 is the Boolean expression in the sum of products from for a logical network which will have a 1 output when
X = 0, Y = 1 , Z = 1
X = 1, Y = 1, Z = β—™
X = 1, Y = 0, Z = β—™
X = 1, Y = 1 , Z = 1



158 .
Inputs X Y Z Output F1 Output F2 Output F3 000 0 1 001 0 1 1 010 1 1 1 011 1 0 0 100 0 0 0

159 . The sum of the products expression for the above table will be Y𝒁 + 𝒀Z.

160 . The product of the sum form of expression for the above truth table will be (X +Y) (𝒀 + 𝒁).